Hubungan Motivasi Dan Sikap Dengan Deteksi Dini Kanker Serviks Menggunakan Iva Test Pada Wanita Usia Subur Di Tpmb Bidan Herni Pamulang Tangerang Selatan - Nirmala Harahap (Politeknik Karya Husada, 2023)
Background: cancer or malignancy that occurs in the cervix. Efforts that have been made to control cervical cancer cases are by increasing the early detection, discovery and follow-up of cancer. So that it is expected to improve the quality of life of sufferers and reduce cervical cancer mortality. One of them is by carrying out an IVA examination (Visual Inspection with Acetic Acid) or a pap smear. Purpose: this study aims to determine the relationship between motivation and attitude with early detection of cervical cancer using the IVA test in women of childbearing age at PMB Midwife Herni Pamulang, South Tangerang in 2022. Methodology: The type of research used in this study was an analytic study with a cross-sectional design. . The sampling technique was carried out by accidental sampling technique. Results: there is a relationship between motivation and early detection of cervical cancer with a P-value of 0.000 and there is a relationship between attitude and early detection of cervical cancer with a P-value of 0.000. Conclusions and Suggestions: There is a variable description of Early Detection of Cervical Cancer with IVA Test on negative motivation and no complaints of 33.7% and there is a relationship between motivation and attitude and Early Detection of Cervical Cancer with IVA Test ρ=0.000. Suggestion: For TPMB Midwives Herni: There needs to be a breakthrough to increase the motivation and attitude of the community so that they are willing to carry out early detection of cervical cancer before complaints occur.